Culinary practices mimicking a polysaccharide-rich recipe enhance the bioaccessibility of fat-soluble micronutrients. (1st November 2016) - Dhuique-Mayer, Claudie; Servent, Adrien; Descalzo, Adriana; Mouquet-Rivier, Claire; Amiot, Marie-Josèphe; Achir, Nawel
Highlights: Carotenoid bioaccessibility from a complex emulsion during cooking. Fibers and oil-in water emulsion implie significant changes of carotenoids and tocopherol content during processing. Increase of lutein micellarization because of heat treatment and structural modifications. Increase of lycopene and β-carotene diffusion in oil phase could improve their bioavailability in vivo. Abstract: This study was carried out to assess the impact of heat processing of a complex emulsion on the behavior of fat soluble micronutrients (FSM) in a traditional Tunisian dish. A simplified recipe involved, dried mucilage-rich jute leaves, tomato paste and olive oil, followed by a cooking treatment (150 min). Hydrothermal pattern and viscosity were monitored along with the changes of FSM content and the bioaccessibility (called micellarization, using an in vitro digestion model). Partitioning of carotenoids differed according to their lipophilicity: lycopene, β-carotene and lutein diffused to the oil phase (100%, 70% and 10% respectively). In contrast with the poor carotenes/tocopherol bioaccessibility (0.9–1%), the highest micellarization was observed for lutein (57%) and it increased with heating time and viscosity change. Domestic culinary cooking practices probably increase the bioavailability of carotenes mainly by their diffusion to the oil phase, facilitating their in vivo transfer into micelles.